The Comparative Method in Synchronic Linguistics: The Case of Word Order - Giorgi, Alessandra (Armenian Folia Anglistika, 2020)
In this article I discuss the comparative method in formal linguistics when applied to word order phenomena in Italian, English and German. I argue that the comparison has to rest on sound theoretical basis in order to reach interesting conclusions. These languages might prima facie all look Subject- Verb-Object – SVO – languages, with some puzzling issues arising in German. At a closer look however, I will show that English and Italian pattern together as their basic word order – i.e., SVO – goes, as opposed to German, an SOV language. Conversely, English and German pattern together with respect to a property typical, even if not exclusively so, of Germanic languages, i.e. Verb Second.
Keywords: word order; syntax; Verb Second; Romance; Germanic